Perancangan Dan Pengembangan Sunshield Handguard Sebagai Pelindung Tangan Pengendara Motor Berbasis Zero Energy - Dinda Dwi Aprilia; Achmad Ramzi; Tan Evan Tandiyono (CV. SINAR HOWUHOWU, 2026)
The rising number of motorcycle riders in Indonesia is accompanied by significant exposure to sunlight, which can cause discomfort, fatigue, and impaired concentration while riding. A rider's hands are particularly vulnerable to direct heat exposure. This study aims to design and develop the